CERUMENOLYTIC AGENTS FOR CERUMEN IMPACTION TREATMENT: A SCOPING REVIEW - Arsyada Hakama Syakuro; Asti Widuri; Rizka Fakhriani; Deoni Daniswara (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2025)
Background: Cerumen impaction is a common condition all over the world. It is observed in around 5% of adults and has a higher prevalence in children, the elderly, and people with intellectual impairment. The management of cerumen impaction must be treated by general practitioners regarding insurance policies in Indonesia. Besides cerumen removal, in difficult cases for cerumen extraction, we can use cerumenolytic agents. Objective: This scoping review is to identify the current data on cerumenolytic drugs, emphasizing their effectiveness, safety profiles, and optimal treatment practices. Methods: Electronic databases were searched for medicinal treatment of cerumen impaction. The search technique entailed querying three esteemed databases—PubMed, SCOPUS, and ScienceDirect—utilizing the following search terms: (cerumen impaction) OR (cerumen prop) OR (cerumen obturans) OR (earwax) AND (cerumenolytic agent). Results: Ex vivo and in vitro studies demonstrated that carbamide peroxide had significantly more rapid cerumen degradation than phenol glycerol, distilled water was superior to commercial agents, and sodium bicarbonate surpassed docusate sodium, and potassium hydroxide had the quickest disintegration among the agents studied. In vivo investigations validated these patterns, with glycerin-hydrogen peroxide attaining the highest rates of tympanic membrane visualization and sodium bicarbonate demonstrating comparable efficacy to docusate sodium. Conclusion: Sodium bicarbonate was the most evaluated cerumenolytic agent, followed by docusate sodium and distilled water. There was no significant difference in weight growth or disintegration between sodium bicarbonate and docusate sodium, while wet cerumen exhibited a more rapid response than dry cerumen.